Storytelling in Higher Education: Comparing Expectancy- Value in Task-Exposed and Non-Exposed English Learners - Wang, Ran (Journal of Language Learning and Assessment, 2024)
Purpose This research aimed to investigate the impact of storytelling with higher complexity on English majors’ attitudes and expectancy-value for tasks from the perspectives of their perception, confidence, challenge, and motivation.   Methodology This quasi-experimental research exposed three storytelling tasks to English majors (N=73) in the experimental group and assigned two control groups(N=74, 152) without storytelling task intervention. Along with and after the experiment, a questionnaire for attitudes and expectancy-value toward storytelling tasks in English learning was administered to English majors (N=299) in the three groups from private and vocational colleges in Guangzhou. Quantitative data was collected through the questionnaire.   Results/Findings The results showed that many English majors considered storytelling simple and childish, disregarding its role in shaping personal experiences and world values. However, exposure to complex storytelling tasks heightened the challenge of accomplishing the tasks, thus leading to a decline in their overall expectancy and value toward tasks. Students without exposure to complex storytelling tasks, regardless of self-reported relevant experience, demonstrated higher and non-significant differences in expectancy-value components, except challenges. The study emphasized the alignment of storytelling tasks with English majors’ career objectives, highlighting the role of storytelling in narrative.   Implications The results contribute to a theoretical understanding of storytelling in higher education and provide practical insights into designing storytelling tasks for English learners at an advanced level.